Preanalytical impact of sample handling on proteome profiling experiments with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Findeisen, Peter; Sismanidis, Diamandula; Riedl, Martin; Costina, Victor; Neumaier, Michael (Clinical chemistry, 2005)
Mass spectrometry (MS) offers a wide range of possibilities for analyzing biological samples containing complex mixtures of proteins and peptides, by generating proteome profiles. The aim of most profiling experiments is identification of changes in protein patterns that are related to a certain disease or clinical status and might therefore be used to improve diagnosis, staging, and monitoring (1). Reproducibility of spectra generated by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS is crucial (2), however, and early enthusiastic reports about the diagnostic power of proteome-profiling approaches for early disease classification have recently been critically assessed and reevaluated (3). The reproducibility of profiling experiments depends on sample quality, which in turn is greatly influenced by preanalytical storage conditions and the choice of anticoagulants (4)(5)(6). In this study, we examined the impact of preanalytical sample handling and storage times on MALDI-TOF MS data for serum and plasma samples and identified a candidate marker to allow objective classification of given samples with respect to age and, hence, appropriateness for MS protein profiling and interpretation of data.
Gesehen am 30.06.2022